NILAI HISTORIS KOMPLEK MAKAM SUNAN KUDUS SEBAGAI BAHAN PENGEMBANGAN SUMBER BELAJAR SEJARAH LOKAL - Indra F, Dedik Agus; Djono, Djono; Isawati, Isawati (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2017)
The goal in this research to describe and find out: (1) the history of the establishment of the Tomb complex of Sunan Kudus, (2) the structure and function of the Building complex of Sunan Kudus, (3) Historical values contained in the Tomb complex of Sunan Kudus who can serve as learning resources local history, (4) the role of the Government is to facilitate Students in harnessing the complex of Sunan Kudus as learning resources local history.Form of research using qualitative, descriptive, qualitative descriptive is a way in researching an event by generating descriptive data. The data source used is the events, places, documents, and informants. Data collection techniques used are observation, interviews, and analysis of data/documents. The sampling technique used is purposive and time sampling. This research, to find the validity of data used two techniques of triangular triangular triangular is a data and methods. Data analysis technique used is the interactive analysis, is move between three components which include the reduction of the data, the presentation of data, and verification/withdrawal of the conclusion.Based on the results of this research can be drawn the conclusion: (1) the history of the establishment of the Tomb complex of Sunan Kudus is a business form of Sunan Kudus to spread islam in the Kudus City that uses how acculturation between Islamic teachings and Hindhu (2) the structure of the building complex of Sunan Kudus is composed of several buildings such as Tower, mosques and Tombs contained in one area and have their respective functions. (3) the values contained in the building complex of Sunan Kudus have much teaching in various fields including political, ideological, economic, social and cultural. (4) Kudus County Government has a role in giving facilities to the learners to utilize complex of Sunan Kudus.